2003
DOI: 10.1021/bi035396g
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the Conserved Active-Site Tyrosine Changes a Retaining Sialidase into an Inverting Sialidase

Abstract: Mutagenesis of the conserved tyrosine (Y370) of the Micromonospora viridifaciens sialidase changes the mechanism of catalysis from retention of anomeric configuration to an unprecedented inverting mechanism in which water efficiently functions as the nucleophile. Three mutants, Y370A, Y370D, and Y370G, were produced recombinantly in Escherichia coli, and all are catalytically active against the activated substrate 4-methylumbelliferyl alpha-D-N-acetylneuraminide. The Y370D mutant was also shown to catalyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 35 publications
7
134
0
2
Order By: Relevance
“…However, as the authors stress (31), the high residual activities for the nucleophile mutants might be a trait of this particular bacterial sialidase, because equivalent mutations in other sialidases result in complete inactivation. Furthermore, the catalytic rates of the mutants are critically dependent on the aglyconeleaving group ability in contrast to the behavior of the wild-type enzyme, which shows higher k cat values (Ͼ10 4 ) when working with natural substrates, such as ␣-2,6-and ␣-2,3-sialyl-lactose (29,31). In the absence of the naturally selected nucleophilic tyrosine, which is strictly conserved in all known exosialidases, compensation by alternative chemical groups appears to take place on the M. viridifaciens mutants, with reaction occurring via several different mechanisms (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the authors stress (31), the high residual activities for the nucleophile mutants might be a trait of this particular bacterial sialidase, because equivalent mutations in other sialidases result in complete inactivation. Furthermore, the catalytic rates of the mutants are critically dependent on the aglyconeleaving group ability in contrast to the behavior of the wild-type enzyme, which shows higher k cat values (Ͼ10 4 ) when working with natural substrates, such as ␣-2,6-and ␣-2,3-sialyl-lactose (29,31). In the absence of the naturally selected nucleophilic tyrosine, which is strictly conserved in all known exosialidases, compensation by alternative chemical groups appears to take place on the M. viridifaciens mutants, with reaction occurring via several different mechanisms (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…Retaining NA mechanisms, on the other hand, appear to be quite distinct. Biochemical analysis of NA from various microorganisms has revealed that a conserved active-site tyrosine can function as a nucleophile and may be the most important catalytic residue [17][18][19] .…”
mentioning
confidence: 99%
“…A tyrosine residue is a neutral nucleophile, but requires a general base to enhance its nucleophilicity. This mechanism was implied from X-ray structures, and was supported by experiments involving trapping of the intermediate with fluoro sugars followed by peptide mapping and then crystallography [6,7], and also through mechanism studies on mutants [8] (Figure 7). …”
Section: Alternative Nucleophilesmentioning
confidence: 74%
“…As members of Clan GH-A they have a classical (α/β) 8 TIM barrel fold with the two key active site glutamic acids being approximately 200 residues apart in sequence and located at the C-terminal ends of β-strands 4 (acid/base) and 7 (nucleophile) [15,16].…”
Section: Three-dimensional Structures Of Gh1mentioning
confidence: 99%